External Ophthalmomyiasis Report in Jordan Valley (Veterinary Science Development, 2014)
A young farmer from Northern Jordan Valley in close contact with sheep was infected acci- dentally in early May 2014 with the larvae of oestrus ovis. The deposition of larvae in his eye lead to inflammation accompanied with severe pain and irritation. The inflammatory signs disappeared five days after receiving the medical care. The infection is more prevalent in almost all ages of males. External ophthal- momyiasis should be considered in susceptible individuals when in contact with sheep or other ruminant species.